Pharmacological management of hypertension in adults: updates from Eighth Joint National Committee - Kamath, Ashwin (International Journal of Basic & Clinical Pharmacology, 2017)
The choice of first-line antihypertensive drug(s) is a matter of intensive research despite the availability of data from large, randomized, and controlled clinical trials. The Eighth Joint National Committee (JNC) guideline on management of high blood pressure (BP) in adults has significant updates over the earlier guidelines.